(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Barbashova I. А. Тhe accumulation of experience children’s sensory development in ancient times. The article deals with evolution of children’s sensory development in ancient times (the emergence of education – IV century), analysis first philosophical justification of value in understanding perception of reality, revealed substantial organizational and methodological potential of purposeful pupil learning perception.